SOCIAL INEQUALITIES: PROBLEMATIKA STRATEGI PENGEMBANGAN DAKWAH DALAM PERSPEKTIF TEORI SOSIAL KONFLIK - Chakim, Sulkhan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
Social inequalities is the factured identities in social life, can be explained from the perspective of social-conflicttheory as an inequality in resource access control in social life, which is caused by various sources, namely the existence ofsocial class, gender, religion, geographical location, race/ethnicity and others. Various sources of social inequality should beused as a base framework for the development strategy by activists proselytizing mission, so the goal can be achievedembodiment Khaira Ummah. In this study, the formulation of development strategy of the Islamic da'wah refers amar ma'rufnahi munkar in the formulation of social reengineering